Dengue fever outbreaks in Eritrea, 2005–2015. Issue 1 (December 2016) - Usman, Abdulmumini; Ball, Jacob; Rojas, Diana; Berhane, Araia; Ghebrat, Yohannes; Mebrahtu, Goitom; Gebresellasie, Azmera; Zehaie, Assefash; Mufunda, Jacob; Liseth, Olivia; Haque, Ubydul; Chanda, Emmanuel
Abstract Background The geographic distribution and burden of dengue is increasing globally. This study aims to evaluate dengue outbreaks and to substantiate the need for strengthened surveillance, reporting and control in Eritrea. Methods Data from two cross-sectional dengue epidemic investigations in 2005 and 2010 were analyzed. Samples were tested for dengue virus-specific IgM and IgG antibodies using capture enzyme-linked immunosorbent assays. Dengue vectors' breeding attributes were characterized and epidemic risk indices determined. National routine surveillance weekly reports from 2005 to the second quarter of 2015 were analyzed for spatiotemporal trends. Results Dengue outbreaks increased in Eritrea from 2005 to 2015 with clinical presentation varying markedly among patients. The house and container indices forAedes aegypti were 40 and 39.6 % respectively, with containers havingA. aeqypti varying significantly (P  < 0.04). Serum from 33.3 % (n  = 15) and 88 % (n  = 26) of clinical dengue cases in Aroget sub-Zoba (district) of Gash Barka Zoba (region) contained anti-DENV IgM antibody in 2005 and 2006, respectively. The national surveillance data from 2005 to 2015 indicate an overall spatiotemporal increase of dengue fever. Conclusions The increase in dengue outbreaks has been confirmed in Eritrea and necessitates strengthening of surveillance and health worker and laboratory capacity, as well as targeted vector control interventions.